PENGARUH PROFITABILITAS, LEVERAGE DAN PERTUMBUHAN PENJUALAN TERHADAP PENGHINDARAN PAJAK (PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023) - Niko Ardiansyah; Dinal Eka Pertiwi; Ahmad Sumarlani (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to examine the effect of profitability, leverage, and seles growth on tax avoidance in LQ-45 companies listed on the indonesia stock exchange for the 2019-2023 period. The population of this study comprises companies listed in the LQ-45 index. The sampling technique used is purposive sampling wiht specific criteria, resulting in a total of 120 samples. The type od data used is secondary data, specifically financial statement obtained from the website https://idx.com.id/, and the analysis method employed is linear regression analysis. The results of this study indicate that profitability has a negative and insignificant effect on tax avoidance, leverage has a positive and significant effect on tax avoidance, and sales growth has a positive effect on tax avoidance. Keywords: Tax Avoidance Profitability Sales Growth.